L’agitation du quotidien - Mariel Acosta; Ernesto Cuba (Glad!)
Ernesto Cuba interviews Mariel Acosta about the findings in her master’s thesis, which investigates inclusive gender morphemes in Spanish-language anarchist publications, among which is the use of @, x and other orthographic innovations that seek to challenge the androcentric bias of language.